2008
DOI: 10.5465/amr.2008.31193163
|View full text |Cite
|
Sign up to set email alerts
|

Carrying too Heavy a Load? The Communication and Miscommunication of Emotion by Email

Abstract: Despite advice to avoid doing so, email senders intentionally and unintentionally communicate emotion. Email characteristics make miscommunication likely, and I argue that receivers often misinterpret work emails as more emotionally negative or neutral than intended. Drawing on the computer-mediated and nonverbal communication, emotion, and perception literature, I introduce a theoretical framework describing what factors make miscommunication most likely, how emotional miscommunication affects organizations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
297
1
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(316 citation statements)
references
References 81 publications
8
297
1
10
Order By: Relevance
“…Surprisingly, however, most research on the communicative nature of emotional expressions has focused on facial displays of emotion. This focus has gone at the expense of attention paid to the informational and communicative functions of vocal, postural, verbal, and symbolic emotional expressions (but see, e.g., Aviezer, Trope, & Todorov, 2012;Byron, 2008;Coyne, 1976;Sauter, Eisner, Ekman, & Scott, 2010;Scherer, 1986;Van Kleef et al, 2004a;Wallbott, 1998). It is clear that facial expressions of emotion play a prominent role in regulating social interaction, but there is no reason to assume that they are unique in serving this function.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, most research on the communicative nature of emotional expressions has focused on facial displays of emotion. This focus has gone at the expense of attention paid to the informational and communicative functions of vocal, postural, verbal, and symbolic emotional expressions (but see, e.g., Aviezer, Trope, & Todorov, 2012;Byron, 2008;Coyne, 1976;Sauter, Eisner, Ekman, & Scott, 2010;Scherer, 1986;Van Kleef et al, 2004a;Wallbott, 1998). It is clear that facial expressions of emotion play a prominent role in regulating social interaction, but there is no reason to assume that they are unique in serving this function.…”
Section: Discussionmentioning
confidence: 99%
“…not bullying), the perpetrator was not to blame and the target deserved it. Coupled with the fact that emotions are particularly difficult to accurately communicate and perceive via email (Byron 2008) and messages via email may increase the potential for misinterpretation (Giumetti et al 2012) empathic understanding may be reduced.…”
Section: Studymentioning
confidence: 99%
“…Sharing life experiences via the telephone or e-mail became an essential component to the relationship for the females in our present study-since they did not have other facets enjoyed by their peers, such as touch, sight, and non-verbal cues. Byron (2008) reported that miscommunication of intended messages is much higher when contact occurs via e-mail than it does when the same messages are transmitted in person. This general principle was enlightened by the findings of our present study.…”
Section: Discussionmentioning
confidence: 99%